Front Cover Picture: Synthesis of Perdeuterated Linoleic Acid‐d31 and Chain Deuterated 1‐Palmitoyl‐2‐linoleoyl‐sn‐glycero‐3‐phosphocholine‐d62 (Adv. Synth. Catal. 21/2022). Issue 21 (13th October 2022) - Moir, Michael; Yepuri, Nageshwar Rao; Marshall, David L.; Blanksby, Stephen J.; Darwish, Tamim A.
Abstract : The front cover image illustrates the successful production of "heavy" deuterated linoleic acid. Deuterium was installed at the beginning of the synthesis via hydrothermal deuteration of readily available saturated fatty acids. The fatty acids were stitched together to ultimately afford the requisite cis, cis‐ skipped diene of linoleic acid. Deuterated linoleic acid is required for the production of labelled biologically relevant linoleoyl lipids, whereby deuteration facilitates various experimental techniques. This was demonstrated by the synthesis of tail deuterated 1‐palmitoyl‐d31 ‐2‐linoleoyl‐d31 ‐ sn ‐glycero‐3‐phosphocholine (PLPC‐d62 ). Details can be found in the Research Article by Darwish and co‐workers (M. Moir, N. R. Yepuri, D. L. Marshall, S. J. Blanksby, T. A. Darwish, Adv. Synth. Catal . 2022, 364, 3670–3681; DOI: 10.1002/adsc.202200616 ).